Persuasive Messages in Stunting Prevention Efforts in Koto Tangah Nagari, West Pasaman Regency - Muhammad Asyraf; Yayuk Lestari; Annisa Anindya (Yayasan Ilomata, 2026)
Stunting remains a major public health challenge in Indonesia, particularly in West Pasaman. This qualitative case study utilizes the Elaboration Likelihood Model (ELM) to examine how stunting prevention messages are processed by caregivers in Nagari Koto Tangah. Data were gathered through interviews with mothers, cadres, and midwives, along with observations and documentation. The study identifies two primary processing routes. Most participants follow the peripheral route, where message acceptance is driven by trust in familiar figures (midwives and cadres), social proximity, or external incentives like social assistance (PKH) requirements. A smaller group engages in central processing, typically those with higher education or personal experience with child nutrition issues. Key findings suggest that technical jargon like